Hamilton-Jacobi formalism to Podolsky electromagnetic theory on the null-plane - Bertin, M. C. (2013)
In this work we develop the Hamilton - Jacobi formalism to study the Podolsky electromagnetic theory on the null-plane coordinates. We calculate the generators of the Podolsky theory and check the integrability conditions. Appropriate boundary conditions are introduced to assure uniqueness of the Green functions associated to the differential operators. Non-involutive constraints in the Hamilton-Jacobi formalism are eliminated by constructing their respective generalized brackets. © 2013 American Institute of Physics.